Developing Cattle Agribusiness in an Intergrated Coconut Plantation Area - Kusuma Diwyanto; S Rusdiana; B Wibowo (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Developing an integrated coconut beef cattle system could be prospective in view of both technical and economical aspects. The present agribusiness of coconut plantation as monoculture, has not met sufficient farmer’s income, because each hectare of land, only produces equivalent to 2,500,000 rupiahs per year. Constraints such as plant disease, fluctuation price of coconut and the large areas of old plants need to be solved seriously. Integrated coconut-cattle system (CCS) in small holding scale region with Low External Input Sustainable Agriculture (LEISA) approach is considered to be economically potential. Additional income is estimated increase 2 – 3 times than traditionally monoculture-based coconut production. About one percent (approximately 30,000 hectare) of total coconut plantation can support 30,000 until 100,000 cattle per year. This will contribute mostly (90%) of the national requirement of meat. Theoritically, when 10% of whole areas of coconut crop is integrated with cattle production, Indonesia could even export the meat.This program of CCS -based on coconut farming can be made posible, when it is supoported by sufficient fund, technology, supervision and condusive policy. Key words: Development, agribusiness, cattle, coconut farm